Gold nanorods etching-based plasmonic immunoassay for qualitative and quantitative detection of aflatoxin M1 in milk. (1st November 2020) - Fang, Bolong; Xu, Shaolan; Huang, Youju; Su, Fengmei; Huang, Zhen; Fang, Hao; Peng, Juan; Xiong, Yonghua; Lai, Weihua
Highlights: Color change and LSPR peak shift of etched AuNRs is used to sensitively detect AFM1. The cut-off value (0.5 ng/mL) for qualitative detection of AFM1 meets FDA's limit. The LOD of the method for detection of AFM1 is 4.1-fold lower than that of ELISA. The method has no cross-reaction with 6 toxins and high recovery (85.08%-108.23%). Abstract: In this study, we developed an indirect competitive plasmonic immunoassay using glucose oxidase (GOx)-induced redox reaction to etch Au nanorods (AuNRs) for qualitative and quantitative detection of aflatoxin M1 (AFM1) in milk. In this system, streptavidin (SA) was selected as a linker between biotinylated anti-AFM1-monoantibody (bio-mAb) and biotinylated GOx (bio-GOx) to form the immunocomplexes bio-mAb-SA-bio-GOx. After the oxidation of the glucose and I -, the resultant I2 could etch cetytrimethylammonium bromide (CTAB)-stabilized AuNRs. This resulted in the blue shift of the longitudinal localized surface plasmon resonance (LSPR) extinction peak, with a color change from blue to pink. The linear range and limit of detection (LOD) of the plasmonic immunoassay were 0.25–10 ng mL −1 and 0.11 ng mL −1, respectively. It displayed quantitative detection with high sensitivity, specificity, recovery, and accuracy, which is promising for qualitative and quantitative detection of AFM1 in food safety.